Using protection motivation theory to predict intention to adhere to official MMR vaccination recommendations in Switzerland - Anne-Linda Camerini; Nicola Diviani; Marta Fadda; Peter J. Schulz (Elsevier, 2019)
Switzerland has not yet reached the measles vaccination coverage of 95 percent that is recommended by the World Health Organization to achieve herd immunity. Within the overall objective of informing effective ways to promote the combined Measles, Mumps, Rubella (MMR) vaccination in Switzerland, the aim of this study was to identify predictors of parents' intention to adhere to official MMR vaccination recommendations. Between October 2012 and January 2013, we surveyed 554 parents of middle school students aged 13 to 15 in Ticino, Switzerland. Guided by Protection Motivation Theory (PMT), the survey covered predictors related to threat and coping appraisal with regards to measles and the MMR vaccine, MMR-related social attitudes and social norms, past experience with the disease and the vaccine, and information sources in the MMR vaccine context. Data were analyzed using Structural Equation Modelling. Among central PMT concepts describing people's threat and coping appraisal, only response (vaccination) efficacy showed to be directly related to parents' intention to adhere to MMR vaccination recommendations (B = .39, p < .001). In addition, social attitudes (B = .38, p < .001) were a direct predictor. Furthermore, social attitudes, social norms, knowing somebody who experienced MMR vaccination side effects, and having sought MMR information from public health institutions, all indirectly predicted parents' intention to adhere to MMR recommendations by activating different threat and coping appraisal mechanisms. To conclude, future communication measures from public health institutions should highlight the altruistic aspect (herd immunity) of the immunization practice as well as present evidence on the high effectiveness of the vaccination in reducing the risk at both the individual and collective levels of getting infected with measles. Keywords: MMR, Childhood vaccination, Protection Motivation Theory, Parents, Switzerland